IBADAH HAJI SEBAGAI PERISTIWA KOMUNIKASI ANTARBUDAYA - Achmad Nashrudin Priatna (Indonesian Journal of Thousand Literacies, 2023)
For Muslims, performing Hajj is a manifestation of the implementation of the pillars of Islam, especially the fifth pillar. Indeed, performing Hajj is commanded in the Holy Qur'an, but this pillar is emphasized on the capable Muslim ummah (manishtatho'a). Physically able (physically and spiritually healthy) and financially capable, considering that the cost of Hajj (ONH) is not small, even every year it always increases. Hajj is carried out only to the Haram land, namely Mecca and Medina located in the Kingdom of Saudi Arabia. Saudi Arabia as a cultural entity, certainly has its characteristics, both language (verbal and non-verbal communication). When Muslims carry out a series of Hajj, of course, open only Muslims from Indonesia, but all Muslims around the world, in accordance with the ratio or quota determined by the Kingdom of Saudi Arabia. Of course as an activity and there are events that accompany it, communication events of course. The communication event is an intercultural communication event because the participants involved in it have the slightest cultural differences. Especially in the momentum of Hajj, various races, nations, and ethnicities mingle in the same time and space. Various cultural differences among pilgrims often lead to misunderstandings that can be fatal. To eliminate these misconceptions, what pilgrims need to do is to realize the uniqueness of the culture of each person, nation, and ethnicity, not be trapped in ethnocentrism, and try to develop empathy